MACHINED PARTS MADE OF TOUGH HARD-TO-CUT ALLOYS (Conferencea, 2023)
The article covers the analysis of components of the cutting errors before choosing the type of control and presents a model of processing error based on analysis of reasons that cause deviation from linear dimensions during machining.